SARS-CoV-2 strains bearing Omicron BA.1 spike replicate in C57BL/6 mice - Ogger, Patricia P.; Martín, Minerva Garcia; Jang, Soyeon; Zhou, Jie; Brown, Jonathan; Sukhova, Ksenia; Furnon, Wilhelm; Patel, Arvind H.; Cowton, Vanessa; Palmarini, Massimo; Barclay, Wendy S.; Johansson, Cecilia (Frontiers in Immunology, 2024)
Introduction SARS-CoV-2, the cause of the COVID pandemic, is an RNA virus with a high propensity to mutate. Successive virus variants, including variants of concern (VOC), have emerged with increased transmission or immune escape. The original pandemic virus and early variants replicated poorly, if at all, in mice at least partly due to a mismatch between the receptor binding domain on the viral spike protein and the murine angiotensin converting enzyme 2 (ACE2). Omicron VOC emerged in late 2021 harboring > 50 new mutations, 35 of them in the spike protein. This variant resulted in a very large wave of infections, even in the face of prior immunity, albeit being inherently less severe than earlier variants. Reflecting the lower severity reported in humans, Omicron displayed attenuated infection in hamsters and also in the K18-hACE2 mouse model. K18-hACE2 mice express both the human ACE2 as well as the endogenous mouse ACE2. Methods Here we infected hACE2knock-in mice that express only human ACE2 and no murine ACE2, or C57BL/6 wildtype mice with SARS-CoV-2 D614G (first-wave isolate), Delta or Omicron BA.1 variants and assessed infectivity and downstream innate immune responses. Results While replication of SARS-CoV-2 Omicron was lower in the lungs of hACE2knock-in mice compared with SARS-CoV-2 D614G and VOC Delta, it replicated more efficiently than the earlier variants in C57BL/6 wildtype mice. This opens the opportunity to test the effect of host genetics on SARS-CoV-2 infections in wildtype mice. As a proof of principle, we tested Omicron infection in mice lacking expression of the interferon-alpha receptor-1 (IFNAR1). In these mice we found that loss of type I IFN receptor signaling resulted in higher viral loads in the lungs were detected. Finally, using a chimeric virus of first wave SARS-CoV-2 harboring the Omicron spike protein, we show that Omicron spike increase infection of C57BL/6 wildtype mice, but non-spike genes of Omicron confer attenuation of viral replication. Discussion Since this chimeric virus efficiently infected C57BL/6 wildtype mice, and replicated in their lungs, our findings illustrate a pathway for genetic mapping of virushost interactions during SARS-CoV-2 infection.